Productivity Growth and Local Content Requirement of the Manufacturing Industry in Banten Province - Yusuf, Diasitta; Firdaus, Muhammad; Asmara, Alla (Universitas Muhammadiyah Yogyakarta, 2021)
Productivity growth needs to be optimized not only to produce quality products, increase exports, and reduce dependence on imports but also to support the performance of the manufacturing sector. This study aims to determine the manufacturing industry map in Banten Province, measure manufacturing industry productivity growth, and analyze the effect of Local Content Requirement (LCR) on manufacturing industry productivity growth from 2005 to 2017 by employing the use of K-Means cluster and panel data regression analysis. For this purpose, Total Factor Productivity (TFP) is the indicator used to measure productivity growth. The LCR is known as the percentage of local raw and auxiliary materials used in the production process. According to K-Means cluster analysis results, industrial companies are grouped into three clusters with different characteristics. The result of panel data regression analysis shows that the TFP of all manufacturing industry sub-sectors has increased and was influenced by LCR, total production, domestic investment, import, and provincial minimum wage. As a result, the government should integrate the LCR and other policies, such as the Indonesian National Standard, to increase productivity growth.